EFFECT OF PHYLLANTHUS NIRURI LEAF EXTRACT AT DIFFERENT DOSES ON THE ANTIBODY TITER RESPONSE TO NEWCASTLE DISEASE IN BROILER - Prawira, I Putu Aditya; Suardana, Ida Bagus Kade; Kardena, I Made; Setiasih, Ni Luh Eka; Nindhia, Tjokorda Sari; Kendran, Anak Agung Sagung (Buletin Veteriner Udayana, 2025)
Newcastle Disease (ND), also known as tetelo, is one of the major poultry diseases that causes significant economic losses in the poultry industry due to decreased productivity and increased mortality rates in broiler chickens. This study aimed to evaluate the effect of Phyllanthus niruri Linn (green meniran) extract at different oral doses on ND antibody titers in broiler chickens. This study employed an experimental method with a completely randomized design, involving 30 broiler chickens divided into three treatment groups: a control group (without extract), a group receiving Phyllanthus niruri extract at a dose of 7 mg/kgW/day, and a group receiving 9 mg/kgW/day for four weeks. ND antibody titers were analyzed using the Hemagglutination Inhibition (HI) test. The results showed that the administration of Phyllanthus niruri extract significantly increased ND antibody titers, with the highest immune response observed in the group receiving 9 mg/kg W/day compared to the 7 mg/kg W/day and control groups. The increase in antibody titers was noticeable from the first week post-vaccination and peaked in the second week. These findings suggest that Phyllanthus niruri extract has potential as a natural immunostimulant to enhance immune responses against ND in broiler chickens. Further studies are needed to evaluate higher doses and the long-term effects of Phyllanthus niruri extract administration on the health and productivity of broiler chickens.